PENGARUH PERSONAL COST DAN TINGKAT KECURANGAN TERHADAP MINAT MELAKUKAN WHISTLEBLOWING DENGAN SIKAP TERHADAP WHISTLEBLOWING SEBAGAI VARIABEL MODERASI - Panca Wahyuningsih; Siti Alliyah; Prihasantyo Siswo Nugroho (Jurnal Akuntansi dan Pajak, 2022)
This study aims to examine the effect of personal cost, the level of fraud, on whistleblowing with an attitude towards whistleblowing as a moderating variable on the Auditor (Case Study on Public Accountant Firm Auditors in Semarang).This study uses primary data with a survey method obtained through a questionnaire. The population is the auditors who work at the Public Accounting Firm in Semarang. The number of samples of 120 respondents who were taken using purposive sampling technique. This research model is descriptive quantitative using explanatory research type. The data analysis technique used Partial Least Square (PLS).The results of the study partially show that personal cost has a significant positive effect on whistleblowing with a coefficient of 0.236 and a P value of 0.007, the level of fraud has a significant effect on whistleblowing with a variable coefficient value of 0.033 and a P value of 0.039. The attitude variable towards whistleblowing is not a moderating variable for the interaction between the personal cost variable and whistleblowing of 0.088 with a P value of 0.184 and the moderating variable for the interaction between the variable level of cheating and whistleblowing with a coefficient of 0.020 with a P value of 0.028.